Novel infusion strategy reduces severe adverse events caused by the anti-GD2 monoclonal antibody naxitamab - Varo, Amalia; Castañeda, Alicia; Chamorro, Saray; Muñoz, Juan Pablo; Gorostegui, Maite; Celma, Mónica S.; Lopez, Sandra; Simao, Margarida; Perez-Jaume, Sara; Mora, Jaume (Frontiers in Oncology, 2023)
Introduction Anti-disialoganglioside 2 (anti-GD2) monoclonal antibodies (mAbs) are associated with Grade ≥3 (≥G3) adverse events (AEs) such as severe pain, hypotension, and bronchospasm. We developed a novel method of administering the GD2-binding mAb naxitamab, termed “Step-Up” infusion (STU), to reduce the risk of AEs of severe pain, hypotension, and bronchospasm. Methods Forty-two patients with GD2-positive tumors received naxitamab under “compassionate use” protocols and administered via either the standard infusion regimen (SIR) or the STU regimen. The SIR comprises a 60-min infusion of 3 mg/kg/day on Day 1 of cycle 1 and a 30- to 60-min infusion on Day 3 and Day 5, as tolerated. The STU regimen uses a 2-h infusion on Day 1, initiated at a rate of 0.06 mg/kg/h during 15 min (0.015 mg/kg) and which increases gradually to a cumulative dose of 3 mg/kg; on Days 3 and 5, the 3-mg/kg dose is initiated at 0.24 mg/kg/h (0.06 mg/kg) and delivered in 90 min according to the same gradual-increase strategy. AEs were graded according to Common Terminology Criteria for Adverse Events version 4.0. Results The frequency of infusions with an associated G3 AE was reduced from 8.1% (23/284 infusions) with SIR to 2.5% (5/202 infusions) with STU. The odds of an infusion being associated with a G3 AE reduced by 70.3% with STU vs. SIR (odds ratio: 0.297; p = 0.037). Mean serum naxitamab levels pre- and post-STU (11.46 µg/ml pre-infusion; 100.95 µg/ml post-infusion) were within the range reported for SIR. Discussion The comparable pharmacokinetics of naxitamab during SIR and STU may indicate that switching to STU reduces G3 AEs without impact on efficacy.